Eating behaviour and eating disorders in individuals with rare neurodevelopmental variants: current knowledge and future research directions - Chawner, Samuel J. R. A. (Frontiers in Psychiatry, 2025)
Rare neurodevelopmental copy number variants (ND-CNVs) have been implicated in a range of psychiatric and neurodevelopmental conditions. Despite their known association with a range of behavioural outcomes, the role of ND-CNVs in eating disorders and related traits remains underexplored. This perspective synthesises current knowledge on the association between ND-CNVs, eating disorders and eating behaviour, highlighting the potential for research into ND-CNVs to provide insights into the genetic architecture of eating disorders. Initial CNV genome-wide association studies have been conducted for anorexia nervosa, and there is now a need to investigate the roles of ND-CNVs in larger samples and across a range of eating disorders. Population cohort studies, and genetic-first designs whereby individuals with a clinical genetic diagnosis undergo deep phenotyping, provide strong evidence for the impact of ND-CNVs on body mass index (BMI), with some ND-CNVs associated with increased BMI, and others decreased BMI relative to the population. Although there have been detailed characterisations of eating behaviour phenotypes in Prader-Willi Syndrome and 16p11.2 Deletion and Duplication Syndromes, overall population and genetic-first studies of the impact of ND-CNVs on eating behaviour and eating disorder risk have been limited. Key research gaps to overcome include the lack of relevant eating disorder phenotype data in large-scale cohorts, limited research into the mechanistic pathways between genotype and phenotypic outcome, and the need for research to include diverse populations. Cross-disciplinary collaboration will be essential to advance the field to enable the development of effective interventions and genetic counselling for eating behaviour and eating disorders.